Incipient colonisation of Lutzomyia longipalpis in the city of Resistencia, province of Chaco, Argentina (2010-2012) - Szelag, Enrique Alejandro (2014)
Lutzomyia longipalpis was recorded for the first time in Argentina in 2004, in the province of Formosa. In the following years, the vector spread to the south and west in the country and was recorded in the province of Chaco in 2010. From November 2010-May 2012, captures of Phlebotominae were made in the city of Resistencia and its surroundings, to monitor the spread and possible colonisation of Lu. longipalpis in the province of Chaco. In this monitoring, Lu. longipalpis was absent in urban sampling sites and its presence was restricted to Barrio de los Pescadores. This suggests that the incipient colonisation observed in 2010 was not followed by continuous installation of vector populations and expansion of their spatial distribution as in other urban centres of Argentina.